Central pattern generator based control for human lower limb movements with functional electrical stimulation - Zhang, Dingguo (2008)
This thesis aims to study central pattern generator (CPG), and model its key mechanisms to design a control system for the human lower limb movement control via functional electrical stimulation (FES). The neural control mechanism of biological motor system is borrowed, which is the kernel of this work.